Waqf New Form (WNF): an elucidation for systematic Wāqf land registration in Malaysia - Ghazali, Noor Azimah; Sipan, Ibrahim; Jalil, Rohaya; Che Yaacob, Ahmad; Haji Mohammad, Mohammad Tahir Sabit (Kulliyyah of Economics and Management Sciences, International Islamic University, Malaysia, 2022)
This paper proposes the Waqf New Form (WNF), adapted from Ghazali, (2021), as a solution to the issues in registering wāqf land in Malaysia. These include problematic registration methods and procedures, conflicts with the civil court jurisdiction,and idle wāqf land. The form is developed based on findings synthesized from a qualitative content analysis involving semistructured interviews with legal practitioners, lecturers, and executive officers in charge of wāqf land matters, as well as a review of official documents from wāqf authority such as the Department of Waqf, Zakat, and Hajj Malaysia (JAWHAR). Results of qualitative analysis have indicated the need for a new registration procedure for wāqf land in Malaysia. The procedure is guided by a new application form consisting of three segments, namely, i) the application details (background of applicant, property, wāqf purpose, and authorized signatures), ii) statutory declaration, and iii) checklist declaration. The WNF has been validated by experts and promoted to be enacted under the National Land Code (NLC) in the near future. Consequently, it will secure the rights of the property with the effects of being perpetual, inalienable, and irrevocable.